Factors influencing Southern Thai women entrepreneurs’ success - Tantasuntisakul, Warangkana; Md Isa, Filzah; Yamaqupta, Narueban (INSInet Publications, 2015)
Background: Women entrepreneurs make a significant contribution to employment, innovation and prosperity of a nation, including Thailand however, was contributed by various factors such as individual, organizational and environmental factors that are surrounding them.Objective: objective of this study is to examine personal factors, social factors, and organizational factors which influence Southern Thai women entrepreneurs’ success.Results: both subjective and objective business performance have shown significant and positive associations with seven independent variables namely motivation, risk taking, work-family balance, management, marketing, financial, and operational.Conclusion: The findings of this study has revealed the importance of personal and organizational factors to the success of women entrepreneurs in Thailand. Based on this study more research can be triggered by other authors to further understand various other factors effecting women entrepreneurs.